Scientific Freedom - Cappato, Marco; Coggon, John; Giordano, Simona (Bloomsbury Academic, 2012)
I‰Scientific Freedom/I‰ represents the first comprehensive anthology of essays designed to explore both the state of scientific progress and the ethics, law and history of scientific research. The book gives readers a fascinating range of perspectives on matters of scientific research that directly affect each and every one of us. The collection aims to improve understanding of ethical, legal, social and political issues surrounding freedom of scientific research and will evaluates ways in which national and international policies can impact upon individuals' access to cures and technologies, and change forever human life, death, and flourishing. With contributions from Nobel Laureates, representatives of patients' associations, scientists, scholars and politicians, Scientific Freedom provides a concise and comprehensive view of the limitations and dangers facing the future of innovation and scientific progress.